Comparative Assessment of Grassland NPP Dynamics in Response to Climate Change in China, North America, Europe and Australia from 1981 to 2010. (6th August 2014) - Gang, C.; Zhou, W.; Wang, Z.; Chen, Y.; Li, J.; Chen, J.; Qi, J.; Odeh, I.; Groisman, P. Y.
Abstract Although climate change has been modifying grassland ecosystems for a long time, few studies on grassland ecosystems have focused on large‐scale responses to climate change. Hence, grassland net primary productivity (NPP) from 1981 to 2010, as well as its variations in China, North America, Europe and Australia, was assessed and compared using a synthetic model in this study. Subsequently, the correlations between the NPP of each grassland type and climate factors were evaluated to reveal the responses of grassland eco‐systems to climate change. The results showed that North America, which has the largest area of grassland ecosystems, exhibits maximum grassland NPP of 4225.30 ± 215.43 Tg DW year−1, whereas Europe, which has the least area of grassland ecosystems among the four regions, exhibits minimum grassland NPP of 928.95 ± 24.68 Tg DW year−1. Grassland NPP presented an increasing trend in China and Australia, but decreasing in Europe and North America from 1981 to 2010. In addition, grassland NPP is positively correlated with mean annual precipitation, but demonstrates notable differences with mean annual temperature. In conclusion, climate change has a significant role in explaining the spatiotemporal patterns of and the variations in grassland NPP in the four regions.